2020
DOI: 10.1101/2020.10.28.358820
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modelling disease transmission from touchscreen user interfaces

Abstract: The extensive use of touchscreens for all manner of human-computer interactions has made them plausible instruments of touch-mediated disease transmission. To that end, we employ stochastic simulations to model human-fomite interaction with a distinct focus on touchscreen interfaces. The timings and frequency of interactions from within a closed population of infectious and susceptible individuals was modelled using a basic queuing network. A pseudo reproductive number (R) was used to compare outcomes under va… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In a initial attempt at a QMRA for touch screens [ 40 ], a complex network of TUI interactions was simulated. It suggested that parameters such as pathogen infectivity and survival time as well as the rate of surface decontamination play an important role in determining risk.…”
Section: Introductionmentioning
confidence: 99%
“…In a initial attempt at a QMRA for touch screens [ 40 ], a complex network of TUI interactions was simulated. It suggested that parameters such as pathogen infectivity and survival time as well as the rate of surface decontamination play an important role in determining risk.…”
Section: Introductionmentioning
confidence: 99%